2022
DOI: 10.1002/cche.10541
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization and functional properties of flours from North‐western Argentina bean (Phaseolus vulgaris L.) cultivars

Abstract: Background and Objectives Beans are widely consumed throughout the world, usually as whole seeds. However, its use as flour is not widely used and they could be potential ingredients for developing new products due to their nutritional, physicochemical, and techno‐functional properties. In this sense, these properties of flours obtained from different agronomic‐improved North‐western Argentina (NOA) bean cultivars were studied. Findings All of the bean flours were rich in total dietary fiber and proteins, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Yao et al (2019) reported that the gelatinization temperatures of mung bean starches derived from four mung bean cultivars varied within the range of 1–3°C ( T o of 62.15–64.45°C; T p of 67.40–68.40°C; T c of 72.40–73.10°C). Nevertheless, biphasic endotherms with T p1 of 70–82°C and T p2 of 90– 105°C were found by heating a suspension of flours from other beans, peas, and lentils (Chung, Liu, Hoover, et al, 2008; Chung, Liu, Pauls, et al, 2008; Nagai et al, 2022; Sánchez‐Arteaga et al, 2015; Santiago‐Ramos et al, 2018). According to previous studies, the first peak is mainly involved in starch gelatinization, while the second peak is related to protein denaturation and melting of the amylose−lipid complex.…”
Section: Resultsmentioning
confidence: 99%
“…Yao et al (2019) reported that the gelatinization temperatures of mung bean starches derived from four mung bean cultivars varied within the range of 1–3°C ( T o of 62.15–64.45°C; T p of 67.40–68.40°C; T c of 72.40–73.10°C). Nevertheless, biphasic endotherms with T p1 of 70–82°C and T p2 of 90– 105°C were found by heating a suspension of flours from other beans, peas, and lentils (Chung, Liu, Hoover, et al, 2008; Chung, Liu, Pauls, et al, 2008; Nagai et al, 2022; Sánchez‐Arteaga et al, 2015; Santiago‐Ramos et al, 2018). According to previous studies, the first peak is mainly involved in starch gelatinization, while the second peak is related to protein denaturation and melting of the amylose−lipid complex.…”
Section: Resultsmentioning
confidence: 99%
“…Starch microstructures were observed in a scanning electron microscope (SEM, FEI Quanta 200, Hillsboro, OR, USA) and granule sizes were determined from at least ten granules following the methodology of Nagai et al 4 Starch selected chemical composition Ash, protein and moisture levels were measured in duplicate according to the AOAC official methods. 7…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The polymorph types of the isolated starch samples were determined according to Nagai et al 4 using an X-ray diffractometer (XEUSS, 1.0, Xenocs, Sassenage, France). The X-ray profiles were analyzed using OriginPro 9.0 software (OriginLab Corporation, Northampton, MA, USA), and the relative crystallinity (RC, %) was calculated as the ratio between the area of the peaks corresponding to the crystalline area and the total area (crystalline + amorphous):…”
Section: Wide-angle X-ray Diffraction (Waxs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Respecto a los compuestos polifenólicos totales evaluados en ambas harinas (Tabla 3.3), los niveles detectados fueron bajos pero significativamente mayor (P < 0,05) en la harina de poroto variedad Cerrillos. Estos resultados son consistentes con lo encontrado en otros trabajos que destacan los bajos contenidos de CFT en harinas de porotos de variedades blancas en comparación con variedades coloreadas (Campos-Vega et al, 2010;Madhujith et al, 2004;Nagai et al, 2022;Rodríguez Madrera et al, 2021).…”
Section: Cerrillosunclassified